Reframing Work Flexibility: The Mediating Influence of Polychronicity on Job Performance Among Gen-Z - Athene, Nugrahani Citra; Prabawani, Bulan (UNIVED Press, 2026)
This study aims to reframe the concept of work flexibility by analyzing its impact on job performance through the mediating role of polychronicity. The research focuses on Gen-Z employees working in the creative industry of DKI Jakarta that known by their adaptive work styles and multitasking tendencies. A quantitative approach was employed using data collected from 120 respondents of Gen-Z through purposive sampling and the analysis conducted using PLS-SEM. The results reveal that work flexibility has a positive and significant effect on job performance, indicating that flexible work arrangements can enhance employees’ productivity. However, polychronicity does not significantly mediate the relationship between work flexibility and job performance, suggesting that multitasking preferences does not necessarily amplify performances. These findings emphasize that while flexibility remains a crucial driver of performance, the alignment between individual time preferences and task structure may not always strengthen its impact. This study contributes to the understanding of how flexibility and time-use orientation interact within Gen-Z’s performance on work.